Latissimus Dorsi Myocutaneous Flap Procedure in a Swine Model. Issue 12 (26th November 2021) - Etra, Joanna W.; Fidder, Samuel A. J.; Frost, Christopher M.; Messner, Franka; Guo, Yinan; Vasilic, Dalibor; Beck, Sarah E.; Bonawitz, Steven; Brandacher, Gerald; Cooney, Damon S.
Abstract: Background: As surgical research expands in both breadth and scope, translational models become increasingly important. The accessibility, reproducibility, and clinical applicability of translational models is of vital importance to ensure adequate and accurate research. Though different flap models have been described, the literature lacks an in-depth, technical description of an easy large-animal preclinical model. We here describe the procedure for elevation of a latissimus dorsi flap in a swine. This flap contains muscle and skin that can be isolated on a vascular pedicle, transferred as a free flap, perfused, or innervated/denervated as dictated by the needs of the experiment. Methods: Five different latissimus dorsi flaps were elevated in miniature swine. Careful attention was paid to anatomical landmarks and optimal placement of incision, dissection, and retraction. Temporary ischemia with vascular clamping was performed along with serial digital and infrared imaging both intra- and postoperatively. In three of the flaps with induced ischemia, the animal was observed for a 30-day follow up with daily photodocumentation and intermittent biopsy. Results: A reproducible latissimus flap model was designed with optimized conditions. In the animals in which flaps were followed postoperatively, complete healing was seen within 30 days without evidence of procedure-related ischemia or loss of motor function. Conclusion: We have identified and described a pre-clinical large animal flap model that can be easily reproduced for translational studies of multiple scientific areas including flap-based repair, ischemia, ischemia reperfusion, and operative technique. This provides an important model for ready replication in preclinical studies of many varieties.